ANALISIS SISTEM INFORMASI MANAJEMEN DALAM PENYALURAN KREDIT USAHA RAKYAT (KUR) PADA PT. BANK RAKYAT INDONESIA (PERSEROAN) TBK. UNIT SUMBAWA BESAR - SUHANDARI, HELDA; BAMBANG, BAMBANG; NURABIAH, NURABIAH (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to analyze the management information system in KUR distribution at Bank Rakyat Indonesia Sumbawa Besar unit. The research method used was a qualitative descriptive approach with data collection techniques through interviews. The informants in this research were the head of the KUR section and staff at the Bank Rakyat Indonesia Sumbawa Besar Unit. The results of this research can be concluded that the use of management information systems in KUR distribution at BRI bank is based on several indicators, namely 1). Accuracy with a high level of truth so that the implementation of management information systems can reduce risks and obstacles when carrying out the data validation process 2). Information is also timely to convey information according to target 3). The information is also in accordance with what is provided to ensure that the information presented is in accordance with consumer needs and finally 4). Information must be complete because it will provide effective support for management in managing the organization efficiently and effectively which will have an impact on their attitude of acceptance of the technology and will have a huge impact on employee performance as well as updates or additions to features in the system that allow users to access information. additional or more detailed and ensure that the information presented by the system can be interpreted easily and is used effectively to design mechanisms or features in the KUR management information system in a format that is easy to understand